Strategies to Improve Logistics Cost Efficiency in Indonesia - Nai'la Nursyifa; Annisa Febrianti; Mardhiyyah Cahaya Chalia; Asep Hadian Sasmita (Universitas Pendidikan Indonesia, 2023)
Logistics is one of the important indicators to achieve social justice for all Indonesian people. With an effective, efficient, and competitive logistics process, Indonesia will certainly become a country that can not only fully protect its people but will also certainly be able to spread the impact of world economic growth like Singapore. Therefore, this article aims to help all logistics actors, the government, and all Indonesians to be able to jointly create social justice for all Indonesians by involving vocational training as an engine for forming qualified human resources in the technical field of logistics management process implementation. By exploring using the systematic literature review method and synthetic matrix of various secondary data, it can be found that there are some similarities in the problems and appropriate solutions in increasing the efficiency of logistics costs by maximizing in 4 things, namely, infrastructure, multimodal transportation, dwelling time, and application of application technology